Magnetic resonance imaging and computed tomography in assessment of atherosclerotic plaque. - Fayad, Z; Sirol, M; Nikolaou, K; Choudhury, R; Fuster, V (2004)
The two most promising noninvasive imaging modalities for the study of atherosclerosis are magnetic resonance imaging (MRI) and computed tomography (CT). Both have been shown to be capable of imaging vessel wall structures and differentiating various stages of atherosclerotic wall changes. MRI has been applied in various in vivo human studies to image atherosclerotic plaques in coronary arteries, carotid arteries, and aorta. The latest generation of multidetector row computed tomography (MDCT) systems allows for the noninvasive characterization of different plaque components in various vascular structures. MDCT allows evaluation of the whole arterial vasculature. In addition, MDCT has the ability to visualize the vessel wall and to give a quantitative measurement of calcified and noncalcified plaque. Using either technique, the repeatable, noninvasive study of atherosclerotic disease during its natural history and after therapeutic intervention will enhance our understanding of disease progression and regression. MDCT and MRI, therefore, may help in selecting appropriate treatments.